Pengaruh Pemberian Insentif terhadap Motivasi Kerja Pegawai pada Kantor Lembaga Penjaminan Mutu Pendidikan (LPMP) Bandar Lampung - Aprilianto Amir; Riswati (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2021)
Human resources have a very important role in an agency, for that in order for the agency to achieve goals as expected, high employee motivation is needed. Generating a high employee motivation is not easy to implement. Therefore, employees should be given appropriate incentives so that the desired employee motivation can be achieved. The provision of incentives can be done by providing annual bonuses, employee welfare, and promotions. As for the main problem with this research is